Assessment of SARS-CoV-2 in human semen-a cohort study - Holtmann, Nora; Edimiris, Philippos; Andree, Marcel; Doehmen, Cornelius; Baston-Buest, Dunja; Adams, Ortwin; Kruessel, Jan-Steffen; Bielfeld, Alexandra Petra (Fertility and sterility, 2020)
To investigate the presence of viral RNA in human semen of patients with severe acute-respiratory syndrome coronavirus 2 (SARS-CoV-2) and to evaluate its presence and relevance in semen parameters. Pilot cohort study. University hospital. Thirty-four men were distributed as: 1) patients in convalescence (patients with confirmed SARS-CoV-2 infection in pharyngeal swab according to reverse-transcription polymerase chain reaction [RT-PCR] or antibodies); 2) negative control group (no antibodies); and 3) patients with an acute infection (detection of SARS-CoV-2 in pharyngeal swab). Semen and a blood sample were collected from each individual. Analysis of semen quality according to the World Health Organization standards. Detection of SARS-CoV-2 by RT-PCR in the native semen sample and after density gradient preparation. Confirmation of immunoglobulin (Ig) A und IgG antibodies in the blood. Eighteen semen samples from recovered men were obtained 8-54 days after absence of symptoms, 14 from control subjects, and 2 from patients with an active COVID-19 infection. No RNA was detected by means of RT-PCR in the semen, including semen samples from two patients with an acute COVID-19 infection. Subjects with a moderate infection showed an impairment of sperm quality. A mild COVID-19 infection is not likely to affect testis and epididymis function, whereas semen parameters did seem impaired after a moderate infection. SARS-CoV-2 RNA could not be detected in semen of recovered and acute COVID-19-positive men. This suggests no viral transmission during sexual contact and assisted reproductive techniques, although further data need to be obtained.